2015
DOI: 10.4238/2015.march.27.19
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the FGFR2 gene in Mexican patients with Apert syndrome

Abstract: ABSTRACT. Apert syndrome (AS) is a frequent acrocephalosyndactyly, with autosomal dominant inheritance. AS has been associated with mutations in fibroblast growth factor receptor 2 (FGFR2), and approximately 99% of cases show 2 of the frequent mutations located in exon IIIa (Ser252Trp or Pro253Arg). The purpose of the present study was to describe the mutations in exon IIIa of FGFR2 in Mexican AS patients and the relationships with clinical features. Exon IIIa of FGFR2 from 6 AS patients was amplified by polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Finally, 35 relevant papers were identified for inclusion in the present systematic review; these were then classified, according to publication/topic type, into four categories ( Table 2 ) ( 1 , 2 - 6 , 9 , 12 , 14 , 18 - 20 , 22 , 23 ). The majority of these were cross-sectional studies, and one article was in Spanish language ( 19 ) ( Table 3 ) ( 7 , 8 , 10 , 11 , 13 , 15 - 17 , 21 , 35 , 36 ). Figure 1 details the entire process of the article search and selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 35 relevant papers were identified for inclusion in the present systematic review; these were then classified, according to publication/topic type, into four categories ( Table 2 ) ( 1 , 2 - 6 , 9 , 12 , 14 , 18 - 20 , 22 , 23 ). The majority of these were cross-sectional studies, and one article was in Spanish language ( 19 ) ( Table 3 ) ( 7 , 8 , 10 , 11 , 13 , 15 - 17 , 21 , 35 , 36 ). Figure 1 details the entire process of the article search and selection.…”
Section: Resultsmentioning
confidence: 99%
“…AS is a rare congenital autosomal dominant disorder that is characterized by severe craniosynostosis (premature closure/fusion of multiple calvarial sutures, specifically the coronal suture) and associated with cranio-facial anomalies, including symmetric 2nd to 4th digit syndactyly in hands and feet (partial or complete fusion of the skin and bones of fingers/toes, with a common nail (6); in severe cases, there may occur synostosis of the radius/humerus and shoulder and elbow joints, with ocular (shallow orbits, exophthalmia, strabismus, hypertelorism, and down-slanting palpebral fissures), ear (chronic otitis media, hearing loss), respiratory (obstructive sleep apnea, mouth breathing), skin (acne, excessive sweating), brain (ventriculomegaly, hydrocephalus), and malformations of the corpus callosum and/or limbic structures; in addition, some children may exhibit a mild mental/intellectual deficit, with an average Intelligence Quotient (IQ) of 74, pharyngeal (short in height), and internal organ abnormalities (gastrointestinal, cardiovascular, genitourinary) ( 7 - 10 ). Craniosynostosis leads to a restriction of facial-skeleton anteroposterior growth, from the glabella to the posterior fontanelle, giving rise to the characteristic cone-shaped head of AS ( acrobrachycephaly or turribrachycephaly ) ( 9 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it was observed that syndactyly was more severe and hydronephrosis accompanied the p.Pro253Arg mutation, and cleft palate malformation accompanied the p.Ser252Trp mutation in our cases. In AS, central nervous system anomalies, congenital heart diseases, genital anomalies, aplasia cutis, and excessive sweating may also be observed in addition to craniosynostosis and syndactyly (7,8). In addition, atypical clinical findings including metopic suture synostosis, edema in the fundus oculi, epilepsy, and central apnea have also been described in patients carrying the p.Ser252Trp mutation (9).…”
Section: Discussionmentioning
confidence: 98%
“…Genetic mutations in AS were discovered for the first time in 1995 by Wilkie, et al 2 ; they occur as a result of heterozygous mutations in FGFR2 gene located at 10q25.3-26 4,7 , which encodes a tyrosine kinase receptor gene that regulates multiple cellular activities, such as cell growth, differentiation, and embryonic development 13 . Two adjacent missense mutations-c.755C>G and c.758C>G, resulting in p.Ser252Trp (66%) and p. Pro253Arg (32%) respectively 2,5,8,11,12,14 -are related to AS. These mutations occur in a highly conserved region in the immunoglobulin-like extracellular subdomains of exon IIIa of FGFR2 gene in >98% of the cases of AS 8,11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Two adjacent missense mutations-c.755C>G and c.758C>G, resulting in p.Ser252Trp (66%) and p. Pro253Arg (32%) respectively 2,5,8,11,12,14 -are related to AS. These mutations occur in a highly conserved region in the immunoglobulin-like extracellular subdomains of exon IIIa of FGFR2 gene in >98% of the cases of AS 8,11,14 . The first mutation is tightly associated with a more severe craniofacial phenotype 11,13 and cleft palate 13 , while the second is associated with more severe syndactyly 11,13 .…”
Section: Discussionmentioning
confidence: 99%